LOMBA ROKET AIR: PENERAPAN PEMBELAJARAN FISIKA BERBASIS PROYEK - Intan Irawati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The objective of research was to measure the difference of studentsâ€™ achievement test before and after project based learning. The methodology of research was the experimental method one group pre-test post-test design. The research conducted in MAN (State Islamic High School) 15 Jakarta. The subjects of research were 24 students elevent grade of science-1 on fluid topic. Instruments research were used were worksheets students, instrument assessment water rocket in rubrics form and physics test. The data analysis used T-test. The research found the increasing students achievment from the scores average 52.60 to 81.88. In addition, the N-gain value average was 0.617 in 0.3 â‰¤ g â‰¤  0.7. This value showed N-gain in medium category. The results of the score the N-gain from 6 students (25 %) were in high category score, two students (8.33 %) in low score and 16 students ( 66,67 %) in medium category. Analysis t-test generated that the average the test scores before and after learning were different.Thus can be expressed that the implementation of learning project based learning affecting the amount of the test scores physics students. This study discovered that project based learning had already given an enabling environment for students in create and design technology products. Students also became more active, enthusiastic, critical, creative in learn physics after by project based learning.Keywords: physics , study results , based learning project , students, water rockets.